BIMBINGAN TEKNIS ASPEK PEMASARAN ONLINE BAGI UMKM KABUPATEN BATU BARA - Liharman Saragih; Rosita Manawari Girsang; Pandapotan Simatupang; Fariaman Purba (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this activity is to provide understanding and knowledge to the micro entrepreneurs and about the marketing aspects. With the lecture method, it begins with an analysis of the needs of the problems faced by SMES in Batu Bara Regency, North Sumatra. Marketing problems faces their business especially how they won in competition in developing information technology rapidly. The solution offered for SMES is to provide an understanding of whether market are driven by markets or products. On this basis, an understanding of the importance of market segmentation, online business, online marketing communications and internet distribution channels is provided. The results of the activity show an increase in understanding of business online and they will applied their business activities by utilizing the internet such as social media, etc